Multicultural Values and Pluralism in Islamic Cultural History Textbooks - Huda, Akhmad; Jazariyah, Ita (Yayasan Letiges Konsultan Sosial, 2024)
This study is motivated by the importance of understanding and accepting cultural and religious diversity in education in Indonesia, a country with very high artistic and religious diversity. This research aims to identify and analyze the representation of multicultural values ​​and teaching about pluralism in the learning material. This research examines multicultural and pluralism values ​​in Islamic Cultural History textbooks. Using a qualitative approach with a type of library research. Data was collected through documentation of textbook material. The analysis uses content analysis techniques. The research results show that the Islamic Cultural History textbook has included several aspects of multiculturalism and pluralism. The multicultural values ​​developed in the Islamic Cultural History textbook include the value of tolerance, the value of justice, the value of equality and the value of democracy. This research provides recommendations for curriculum developers and textbook writers to further integrate pluralism and multicultural values ​​more deeply and systematically in learning materials to form a broader and deeper understanding of diversity in Indonesia.